GMJ 2019
DOI: 10.31661/gmj.v8i0.1366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Herbal Mouthwashes Containing Zataria Multiflora Boiss, Frankincense and Combination Therapy on Patients with Gingivitis: A Double-Blind, Randomized, Controlled, Clinical Trial

Abstract: Background: Dental plaques as adhesive microbial aggregates on tooth surfaces are considered the first stage of tooth decay as well as gingivitis. Accordingly, the effect of different antimicrobial mouthwashes on removing dental plaques and preventing their formation has been evaluated in various studies. This study aimed to evaluate the efficacy of herbal mouthwashes containing hydro-alcoholic extract of Zataria multiflora (ZM), Frankincense (FR), and a combination of both (ZM+FR) and compare it with chlorhex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, because the authors used a mix of five natural products, it is not possible to conclude whether B. serrata extracts play a role in the improvement of clinical symptoms. Another study showed that mouthwashes containing natural products, including one with frankincense extracts, improved plaque, gingivitis, and gingival bleeding [64]. These initial studies are encouraging and suggest that clinical trials with larger sample populations and only one natural product (frankincense) are needed to confirm the effects of frankincense against periodontal disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, because the authors used a mix of five natural products, it is not possible to conclude whether B. serrata extracts play a role in the improvement of clinical symptoms. Another study showed that mouthwashes containing natural products, including one with frankincense extracts, improved plaque, gingivitis, and gingival bleeding [64]. These initial studies are encouraging and suggest that clinical trials with larger sample populations and only one natural product (frankincense) are needed to confirm the effects of frankincense against periodontal disease.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies describe clinical trials using frankincense extracts to treat several conditions, such as knee pain [59,60], hepatic inflammation and lipid metabolism [61], and chronic low back pain [62]. Regarding oral health, three publications report the effects of B. serrata extracts in the treatment of periodontitis [63][64][65]. Ardakani et al showed that patients using a mouthwash consisting of five herbal extracts (including B. serrata extracts) improved their periodontal condition in plaque-induced gingivitis comparable to the effect of 0.2% chlorhexidine mouthwash [63].…”
Section: Discussionmentioning
confidence: 99%